INDEPENDENT LEARNING - KEY CHALLENGES IN IMPLEMENTING INDEPENDENT EDUCATION IN HIGHER EDUCATION INSTITUTIONS - Vafaeva Zamira Giyasovna; Gafurova Savlat Tolibovna (Western European Studies, 2026)
This article explores the key challenges and contextual considerations involved in implementing independent education in foreign higher education institutions. Drawing from international examples and scholarly analysis, it evaluates the readiness of both students and institutions to adapt to these new paradigms and proposes ways to enhance the effectiveness of independent learning practices
Keywords: independent study; project-based learning; research tasks